Involving Communities In Conservation: Insights From Manupeu Tanadaru National Park, Indonesia - Miles, Wendy Beth; Permana, Rizki Pandu (Journal of Rural Indonesia [JORI], 2013)
ABSTRACTDeveloping strategies to meet the needs of both human communities and their environment is a complex and challenging task. This is particularly true in Indonesia, the worldâ€™s second most biodiverse and fourth most populous country. Because of the heavy dependence of much of Indonesiaâ€™s population on natural resources, many conservation NGOs have employed â€œparticipatory conservationâ€ mechanisms (e.g. village conservation agreements, participatory mapping, and community conservation groups), designed to involve local people in environmental management and conservation. This paper examines the use of participatory conservation mechanisms during the establishment of Manupeu Tanadaru National Park in Indonesia, and considers the experiences of various stakeholders in the participatory conservation process designed by Burung Indonesia (an Indonesian affiliate organization of BirdLife International). This study highlights common challenges experienced by non-profit organizations working to increase the participation of local people in the establishment and management of protected areas. With participatory mechanisms becoming an integral part of many conservation initiatives, this research provides important insights for conservation practitioners and policy makers. Â© 2013 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Â Keywords: environmental non-governmental organizations, Indonesia, Manupeu Tanadaru National Park,Â participatory conservation